Campus Incivility and Free Speech: A Contemporary Dilemma - Robert E. Cipriano Dr.; Jeffrey L. Buller Dr. (Academic Chairpersons Conference Proceedings, 2022)
The issue of free speech on college campuses is as old as education itself and as current as today's news. Institutions of higher education often find themselves torn between their desire to create environments where students and professors remain physically safe and their mission to protect academic freedom and the right of free speech. This interactive presentation will provide academic leaders with the skill set to increase the likelihood that constructive conflicts between ideas don't escalate into destructive, violent acts.
Keywords: Free Speech; First Amendment; Campus Destructive